Determination of the influence of rosehip powder on the quality of wheat dough and bread - Oliinyk, Svitlana; Samokhvalova, Olga; Bilash, Bohdan; Bolkhovitina, Olena (Technology audit and production reserves, 2026)
The object of the research is the technology of wheat bread. The problem of creating high-quality bakery products using natural non-traditional raw materials with a high content of physiologically functional nutrients is solved. For this purpose, it is proposed to use rosehip powder. The introduction of non-traditional raw materials into the dough affects not only the nutritional value, but also the formation of bread quality. In this regard, the work investigated the effect of rosehip powder on the properties of wheat flour, as well as the processes of dough ripening, organoleptic and physicochemical properties of products. It was found that the introduction of rosehip powder in an amount of 2.0–8.0% to replace wheat flour contributes to the strengthening of gluten, namely, increasing elasticity and reducing gluten extensibility, reducing dough spreading, and improving the gas-holding capacity of the dough. This is explained by the oxidative action of ascorbic acid, the formation of complexes of gluten protein with polyphenols and dietary fibers of rosehip powder. It was found that in the presence of rosehip fruit powder, lactic acid and alcoholic fermentation are activated, which contributes to more intense changes in acid accumulation and gas formation in the dough due to the activation of lactic acid bacteria and baker's yeast in the presence of biologically active substances of the additive. The use of rosehip powder in an amount of 2.0–6.0% contributes to an increase in the specific volume, porosity and elasticity of the crumb, the formation of harmonious taste and aromatic properties of products with characteristic rosehip notes. The introduction of 8.0% of the additive is not recommended, as it leads to the formation of coarser porosity, too sharp sour taste of the additive and crunch. The results obtained can be used in the practice of baking production to develop a technology for bread of increased nutritional value using rosehip powder.